IMPLEMENTASI MAL PELAYANAN PUBLIK (MPP) DI KOTA BEKASI - Irma Ramahyanti Ramahyanti1; Lukmanul Hakim Hakim; Kariena Febriantin Febriantin (Jurnal Pemerintahan dan Politik, 2022)
ABSTRACT The city of Bekasi as one of the cities with a high population growth rate, with a busy schedule of course is a factor causing the low number of administrative compliance, plus the distance between agencies and the length of the process makes the interest of Bekasi residents to take care of administration increasingly low. Departing from this, there was a Public Service Mall with the aim of bringing services closer and easier to the community. As the improvement efforts of the Ministry of Administrative Reform and Bureaucratic Reform on the poor assessment of bureaucratic services caused by pathology. So that the presence of the Public Service Mall with working hours until Saturday is certainly a breath of fresh air in administrative services to the public. So the purpose of this study is to use a descriptive qualitative approach that describes how the process of implementing a Public Service Mall to realize a pathology-free bureaucracy using 3 elements from Charles O Jones, namely organization, interpretation and application. The results showed that the community was enthusiastic and there was an increase in visits, due to clarity and certainty in terms of procedures/mechanisms, time and also costs. It's just that all agencies or private institutions that have direct contact with the community have not been involved. Of course, the involvement of all institutions, both government and non-government, will make it easier for the community and shorten the administrative time. The formation or strengthening of regulations is needed as a basis for movement so that it is able to bind agencies or institutions in the region. Keywords : Administration, Bureaucracy, Public, Public Service Mall, Service  ABSTRAK Kota Bekasi sebagai salah satu kota dengan laju pertumbuhan penduduk yang tinggi, dengan kesibukan yang padat tentu saja menjadi faktor penyebab rendahnya angka taat  administrasi, ditambah jauhnya jarak instansi serta lamanya proses semakin membuat minat warga Bekasi untuk mengurus administrasi kian rendah. Berangkat dari hal tersebut hadirlah Mal Pelayanan Publik dengan tujuan mendekatkan dan memudahkan pelayanan kepada masyarakat. Sebagaimana upaya perbaikan dari Kementerian Pendayagunaan Aparatur Negara dan Reformasi Birokrasi terhadap buruknya penilaian pelayanan birokrasi diakibatkan patologi. Sehingga kehadiran Mal Pelayanan Publik dengan waktu kerja hingga sabtu, tentu menjadi angin segar dalam pelayanan administrasi kepada publik. Sehingga tujuan Penelitian ini menggunakan pendekatan kualitatif deskriptif yang menggambarkan bagaimana proses implementasi Mal Pelayanan Publik untuk mewujudkan birokrasi bebas patologi dengan menggunakan 3 elemen dari Charles O Jones yaitu organisasi, interpretasi dan juga penerapan. Hasil didapat bahwa masyarakat antusias dan terjadi peningkatan kunjungan, dikarenakan adanya kejelasan dan kepastian baik dari segi prosedur/mekanisme, waktu dan juga biaya. Hanya saja belum terlibat keseluruhan instansi atau lembaga swasta yang bersinggungan langsung dengan masyarakat. Tentunya keterlibatan keseluruhan lembaga baik pemerintah atau non pemerintah akan semakin memudahkan masyarakat dan mempersingkat waktu pengurusan administrasi. Pembentukan atau penguatan regulasi diperlukan sebagai landasan gerak sehingga sifatnya mampu mengikat instansi atau lembaga di daerah.  Kata Kunci : Administrasi, Birokrasi, Masyarakat, Mal Pelayanan Publik, Publik